Working with emotions in complementary medicine: the case of aromatherapy practitioners. (2nd January 2007) - Lee-Treweek, Geraldine
Complementary and alternative medicine (CAM) is increasingly popular in the UK (Cant 2004:173). Along with distinct therapeutics, these emerging occupations often allege that they use different notions of the emotions (Campbell, 2002). But without conventional practitioner/patient roles, how do aromatherapists negotiate and manage emotional boundaries? This paper discusses an interview based study with aromatherapists that focused upon how the aromatherapists constructed and worked with emotion at work. Whilst not suggesting that the same issues are important in all forms of complementary medicine, the paper argues that more research is needed to uncover the emotional landscape of CAM practice.